Marine Animal Forests 2016
DOI: 10.1007/978-3-319-17001-5_54-1
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic Versus Non-symbiotic Octocorals: Physiological and Ecological Implications

Abstract: Octocorals are a major component of the sessile benthic fauna worldwide, especially important in tropical regions, such as the Indo-Pacific and Caribbean, where together with hard corals they represent the most common group of macrobenthic animals of coral reefs. Despite their importance, little is known about their physiology, specifically the importance of their symbiotic relationship with the algal endosymbiont from the genus Symbiodinium, and the advantages/ disadvantages associated with this symbiosis. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 85 publications
1
19
0
Order By: Relevance
“…These organisms exhibit composite responses to climatic conditions. Practically ubiquitous in all aquatic habitats, they are characterized by high regenerative capacity and considerable ability to form symbioses with microorganisms (Bosch et al 2014;Sun et al 2016;Schubert et al 2017). They are morphologically simple but with complex gene repertoires able to code much of the sensory capacity of more complex animals (Technau et al 2005;Chapman et al 2010;Srivastava et al 2010;Bosch et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These organisms exhibit composite responses to climatic conditions. Practically ubiquitous in all aquatic habitats, they are characterized by high regenerative capacity and considerable ability to form symbioses with microorganisms (Bosch et al 2014;Sun et al 2016;Schubert et al 2017). They are morphologically simple but with complex gene repertoires able to code much of the sensory capacity of more complex animals (Technau et al 2005;Chapman et al 2010;Srivastava et al 2010;Bosch et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Octocorals are important members of shallow and mesophotic coral reef communities (Schubert et al 2016; Benayahu et al 2019) and create complex three‐dimensional habitats for other reef species (i.e., marine forests— see Rossi et al 2017). Although some symbiotic octocoral species have been reported as mixotrophic in shallow waters (Fabricius and Klumpp 1995), two recent studies performed on gorgonian octocorals have concluded that the extent of autotrophy and heterotrophy depends on host morphology (e.g., colony shape and polyp size) and symbiont specificity (Baker et al 2015; Rossi et al 2018).…”
mentioning
confidence: 99%
“…With a longer dark incubation, as occurring at night within a circadian cycle, the light harvesting capacity can be reduced due to periodical oscillations of light-harvesting protein synthesis on the thylakoid membranes [80]. Photosynthesis to respiration ratio (P/R) can be used as proxy for autotrophic contribution [81]. Our findings (PAR = 500, P/R = 1.4; PAR = 200, P/R = 1.9) are in accordance with the values observed in C. andromeda (P/R = 1.4) [82] and in other zooxanthellate jellyfish such as Linuche and Mastigias (P/R of 1.7 and 1.1-1.8 respectively) [31,32].…”
Section: Plos Onementioning
confidence: 99%